Synchronization of hyperchaos of cellular neural network with applications to secure communication - JIANG Guo ping; WANG Suo ping (Tongxin xuebao)
In this paper,we study the synchronization of hyperchaos in cellular neural network,and present a secure communication system based on hyperchaos of cellular neural network The communication system presented here only needs to transmit a scalar signal,and it is more secure because of the use of hyperchaos